Implementasi Audit Sistem Informasi Akademik Menggunakan Framework Cobit 5.0 - Siti Mutoharoh Permata Ayunda; M. Rizki Auliansyah Ginting; Rafli Pramudia (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Universities that provide educational services, then siakad has a fairly important function in supporting the processing and monitoring of academic data of educational institution. In SIAKAD STMIK XYZ consists of scheduling, filling KRS, studen grades and others. Irrelevantly organized pruning of the academic information system has the potential to cause problems that can jeopardize service affordability, while a reduced level of user satisfaction has the capacity to affect the level of trust from stakeholders. Measurement is needed to evaluate and make the audit result as input to improve the management of the siakad. In this study, data collection was carried out using a survey in the form of a questionnaire. The domains used in this study are DSS AND MEA. The results of the questionnaire were collected and carried out the data analysis stage using the capability level, and gap analysis. The results found the data analysis stage using the capability level with a magnitude of 2.67 which means it is still at level 2. Thus there is a difference of 1.33 to reach the expected level 4. The results of the implementation of the STMIK XYZ academic information system with the cobit 5 framework can be a reference for knowing the weaknesses tat exist in the academic information system so that its performance becomes more optimal.